Health Through a Human Right Lens at the US-Mexico Border: Increasing Access to Healthcare for Central American Immigrants - Venturi, Carolina; Guízar-Sánchez, Diana; Ramos-Tovar, María Elena; Torres, Melissa; Avellaneda, Flor D.; Torres-Hostos, Luis R.; Matuk-Villazon, Omar (Frontiers in Public Health, 2022)
The U.S.-Mexico border is affected by unique socio-historical, demographic and political forces that shape the health of its binational residents. There is a critical need for greater coordination of binational health services, access to quality health care, and addressing health more broadly to include social determinants of health framework. Our paper describes the scope and impact of structural racism in Latino/Mexican communities. We deconstruct the myth of "homogeneity" and describe inter-and intra-group racism and discrimination and its impact on health. We explore attitudes toward racial/ethnic/national identity in health care settings, including the impact of generational status on compassionate care provided by Latino/Mexican providers. We examine available binational health data to better describe existing health disparities, and discuss some evidence-based approaches and solutions.